Genome mapping of postzygotic hybrid necrosis in an interspecific pear population. (6th January 2016) - Montanari, Sara; Brewer, Lester; Lamberts, Robert; Velasco, Riccardo; Malnoy, Mickael; Perchepied, Laure; Guérif, Philippe; Durel, Charles-Eric; Bus, Vincent G M; Gardiner, Susan E; Chagné, David
Abstract: Deleterious epistatic interactions in plant inter- and intraspecific hybrids can cause a phenomenon known as hybrid necrosis, characterized by a typical seedling phenotype whose main distinguishing features are dwarfism, tissue necrosis and in some cases lethality. Identification of the chromosome regions associated with this type of incompatibility is important not only to increase our understanding of the evolutionary diversification that led to speciation but also for breeding purposes. Development of molecular markers linked to the lethal genes will allow breeders to avoid incompatible inbred combinations that could affect the expression of important agronomic tratis co-segregating with these genes. Although hybrid necrosis has been reported in several plant taxa, including Rosaceae species, this phenomenon has not been described previously in pear. In the interspecific pear population resulting from a cross between PEAR3 ( Pyrus bretschneideri × Pyrus communis ) and 'Moonglow' ( P. communis ), we observed two types of hybrid necrosis, expressed at different stages of plant development. Using a combination of previously mapped and newly developed genetic markers, we identified three chromosome regions associated with these two types of lethality, which were genetically independent. One type resulted from a negative epistatic interaction between a locus on linkage group 5 (LG5) of PEAR3 and a locus on LG1 of 'Moonglow', while the second type was due to a gene that maps to LG2 of PEAR3 and which either acts alone or more probably interacts with another gene of unknown location inherited from 'Moonglow'. Abstract : Fruit trees: preventing lethal crosses in pear A newly identified deleterious effect in cross-bred pears could be prevented by identifying the genetic regions involved. Adverse interactions between genes from the two parents of a hybrid—akin to an autoimmune response—can cause dwarfing, tissue damage and death, a phenomenon known as hybrid necrosis. Although recognized in several plant species, it has not before been seen in pears. An international team led by David Chagné of the New Zealand Institute for Plant and Food Research identified two types of hybrid necrosis in pears. Using modern genetic screening techniques, they then located two interacting gene regions causing 'Type 1' necrosis, and one implicated in 'Type 2'; a second region remains to be identified. Their discoveries may shed light on the evolutionary history of pears, and will help breeders select compatible parents when breeding new varieties.